Tourism and economic misery: Theory and empirical evidence from Mexico - Fernando Sánchez López (Economies, 2024)
The misery index (MI) was devised to summarize the most evident costs for a society, attempting to objectively measure the loss in general welfare. It has been remarked in the literature that economic growth exerts a negative impact on the MI; however, analyses of this relationship in the tourism field have been neglected. This study assessed the effectiveness of the tourism sector at improving welfare conditions by measuring the impact of tourism GDP on the misery index and providing a theoretical framework for the relationship between tourism and the MI. A quantitative analysis was conducted using quarterly time series data for the period 2005Q1-2021Q2. Firstly, the existence of a long-term relationship was tested by using the Toda-Yamamoto procedure, and secondly, by applying linear and nonlinear ARDL models. The main results show that tourism can help to reduce the loss of welfare mirrored by the MI. These findings have policy implications, as they provide evidence that expanding the tourism sector counters the MI, and, consequently, the economic malaises derived from it.
Keywords: 330; ARDL; inflation; NARDL; Okun's misery index; tourism GDP; unemployment